PRODUKTIVITAS DAN KUALITAS MADU KELULUT DARI DESA BANGKILING RAYA KABUPATEN TABALONG - Maulana Malik; Siti Hamidah; Trisnu Satriadi (Universitas Lambung Mangkurat, 2023)
The stingless bee (kelulut / Trigona iitama) is a type of insect that is increasingly being cultivated in various regions, including in South Kalimantan. The efficacy of kelulut honey is very good and easy in beekeepng techniques is the reason why kelulut beekeeping has the potential to be developed. The purpose of this study was to determine the productivity and quality of kelulut honey at Bangkiling Raya Village, Tabalong Regency. Honey productivity was measured for 4 consecutive months, starting from June 2021 to September 2021. Honey quality was tested based on SNI 8664:2018, namely water content, diastase enzyme activity and reducing sugar. Honey production each month varies between 208 ml per colony to 344 ml per colony. Some parameters of the quality of the honey produced still do not meet SNI, namely water content, HMF and diastase enzyme activity. Parameters that have complied with SNI are reducing sugars. The results of this study indicate that there is a need for improvement in kelulut beekeeping techniques, harvesting techniques and post-harvest handling.Lebah tanpa sengat (Kelulut / Trigona iitama) merupakan jenis serangga yang mulai marak dikembangkan di berbagai daerah, termasuk di Kalimantan Selatan. Manfaat madu yang baik serta kemudahan dalam teknik budidayanya menjadi alasan mengapa kelulut sangat potensial untuk dikembangkan. Tujuan penelitian ini adalah untuk mengukur produktivitas dan kualitas madu kelulut yang berasal dari Desa Bangkiling Raya, Kabupaten Tabalong. Produktivitas madu diukur selama 4 bulan berturut-turut, mulai dari Juni 2021 sampai dengan September 2021. Kualitas madu diuji berdasarkan SNI 8664-2018 berupa kadar air, enzim diastase, dan gula pereduksi. Produktivitas madu bervariasi antara 208 ml hingga 344 ml per koloni per bulan. Madu kelulut memiliki kadar air, HMF dan aktivitas enzim diastase yang belum memenuhi SNI, sedangkan untuk parameter gula pereduksi sesuai dengan SNI. Pengembangan lebih lanjut perlu dilakukan seperti teknik budidaya, teknik pemanenan dan penanganan pasca panen.